Posisi Asbabun Nuzul dalam Kerangka Hermeneutika Nasr Hamid Abu Zayd dan Hasan Hanafi: Studi Kasus Ayat Tentang Larangan Khamr: Asbabun Nuzul in Nasr Hamid Abu Zayd and Hasan Hanafi's Hermeneutics: A Case Study of Verses on the Prohibition of Khamr - Fina Izzatul Muna; Adi Rahmat Hidayatullah (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2025)
Asbabun nuzul plays a crucial role in the hermeneutical approaches of Nasr Hamid Abu Zayd and Hasan Hanafi. Qur’anic interpretation, which is inherently dynamic, goes beyond literal meanings by emphasizing contextual relevance in contemporary discourse. For progressive exegetes such as Abu Zayd and Hanafi, asbabun nuzul narratives foster socio-historical awareness that prevents rigid, purely linguistic interpretations. This study employs a comparative qualitative method through library research, drawing on both primary and secondary sources including books, theses, and scholarly articles. The research yields two main findings. First, asbabun nuzul functions as a dynamic hermeneutical instrument. Abu Zayd treats it as a methodological step in interpreting the Qur’anic text, whereas Hanafi employs it as a foundational tool for practical engagement. Second, in reconstructing the understanding of the stages of alcohol (khamr) prohibition, Abu Zayd identifies three legislative phases (tasyri') and positions asbabun nuzul as complementary, filling interpretive gaps between verses. In contrast, Hanafi interprets the three related verses as responses to the evolving social reality of Arab society at the time, using asbabun nuzul as a contextualizing mechanism. This comparison highlights their shared commitment to contextual interpretation while reflecting differing emphases in hermeneutical application.